PENGARUH PENERAPAN MODEL PEMBELAJARAN INKUIRI TERHADAP HASIL BELAJAR TEKNIK ELEKTRONIKA DASAR SISWA KELAS X SMKN 5 PADANG - Letty Aryanti; Muhammad Anwar; Zulwisli Zulwisli (Universitas Negeri Padang, 2017)
This research was focusing on the low of student’s learning outcome, specially on Basic Electronics subject at SMKN 5 Padang. The objective is to reveal the effect of applying inquiry learning model to the subject. By using true experimental with simple random sampling; one of probability sampling tecnique, the model wa enducted in experiment class. A control class where STAD type of cooperative learning model, was also implemented to compare the treatment. The primary data was measured by structured test (Pre-test and Post-test) according to basic competences described of the subject. based on the t-test result, complying the pre-requisite test such as normalityexamination, this research found that t>t0 (1,742 > 1,701). However, the result has shown that inquiry learning model is providing better student’s learning outcome than STAD model. Therefore, the inquiry model is more effective than STAD model as research conclusion. Keywords: learning outcomes, learning model, Inquiry, Student Team Achievemnt Division.